2018
DOI: 10.24843/jaa.2018.v07.i01.p10
|View full text |Cite
|
Sign up to set email alerts
|

Kemandirian Petani dalam Mengelola Usahatani Sayuran di Kota Denpasar

Abstract: Self-Reliance of Farmers in Managing Vegetable Farming in Denpasar City The development of urban agriculture has many challenges such as the difficulty ofobtaining production inputs, the difficulty of obtaining credit, the limited ofresources, the limited time, and the agricultural sector which is not a priority sector.Difficulties in farming in urban areas can be minimized with the self-sufficiency ofeach farmer. The purpose of the study was to investigate how the performance ofvegetable farming managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Emery (2015) research results that independence had the effect of covering the structural dependency faced by farmers (such as dependence on creditors). Further strengthened by the results of research by Sucitayasa et al, (2018) the management of vegetable cultivation that performed by farmers in Denpasar City was still traditional. The independence level of farmers in managing vegetable farming in Denpasar City on the capital/ finance, production, and marketing aspects was evenly in the medium category.…”
Section: Economic Condition Happening To the Urban Farmer In Denpasar Citymentioning
confidence: 99%
“…Emery (2015) research results that independence had the effect of covering the structural dependency faced by farmers (such as dependence on creditors). Further strengthened by the results of research by Sucitayasa et al, (2018) the management of vegetable cultivation that performed by farmers in Denpasar City was still traditional. The independence level of farmers in managing vegetable farming in Denpasar City on the capital/ finance, production, and marketing aspects was evenly in the medium category.…”
Section: Economic Condition Happening To the Urban Farmer In Denpasar Citymentioning
confidence: 99%
“…This empowerment directs the farmer to be independent and capable of managing the agribusiness without any subsidies or protection provided by the government. Sucitayasa et al, (2018) in their study on the vegetable farmer population in Denpasar City, had reported a moderate level of independence in the aspect of financial, production, and marketing. Furthermore, Ruhimat (2014) in his study, identified a low level of independence among the farmer population.…”
Section: Introductionmentioning
confidence: 99%